ANALISIS PANCA YADNYA DALAM KONTEKS SAGUNA BRAHMAN DALAM MENCIPTAKAN AKTIVITAS SOSIAL BUDAYA - Made Adi Nugraha Tristaningrat (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Basically Yajna are supporting the world and the universe, due to the nature and humanbeings are created by Hyang Widhi through Yajna. Yajna is not just a religious ceremony, morethan that of all human activities in order to of bhakti hyang Widhi prostration is the Yajna. In theteachings of Hinduism we know the term Saguna Brahman which is Brahman in the eternity oftime that his presence is both a virtual and intangible but active with all of his creation. SagunaBrahman with his this is the pace of change in the sapta ongkara Ejection Wrhaspati Tattwamentioned: Brahman with a sakti, and swabhawanya, he was active with all his creations. SagunaBrahman in Hinduism belief (Panca Sradha) towards the Lord mentioned is described as privateand are reflected in the form of the Almighty by nature the human mind empirically. Empiricallyas culture the culture's very closely related to society and culture contains a whole sense ofsocial values, social norms, science as well as the overall social structures, religious, and others.As one form of execution Yajna in the context of saguna brahman held in Besakih ceremonyPanca Bali Krama i.e. in stiti dharma also mentioned where adoring Sang Hyang Widhi asSaguna Brahman ceremony Panca Bali Krama such intended to invoke the well-being, tranquility,and peace for the Earth and all living beings his joyous